Late Tourniquet Release and Drain Clamping Reduces Postoperative Blood Loss in Total Knee Arthroplasty. Issue 1 (February 2014) - Yildiz, Cemil; Koca, Kenan; Kocak, Necmettin; Tunay, Servet; Basbozkurt, Mustafa
Background: Many studies have investigated the effect of tourniquet release time and closed suction drainage in total knee arthroplasty (TKA). However, controversy remains as to the advisability of preclosure tourniquet release and the advisability of closed suction drain use following total knee arthroplasty. Questions/Purposes: The aim of the study was to investigate if there is a benefit of performing tourniquet release after skin closure, along with drain clamping, for the first 6h following TKA. Methods: Ninety-six patients underwent TKA between May 2009 and April 2010. Fourteen of these were excluded because of systemic diseases and simultaneous bilateral TKA. Twenty-nine of these were excluded due to use of a patellar component and posterior cruciate ligament (PCL)-sacrificing systems. Thus, 53 patients that underwent PCL-retaining cemented TKA were reviewed retrospectively. In the control group (group C), the tourniquet was released before skin closure, an attempt at hemostasis was made, and a compressive bandage was applied. The drain was not clamped in these patients. The test group of 23 patients (group T) had tourniquet release after skin closure and after the compressive bandage was applied. The drain was clamped for the first 6h after surgery. The two groups were compared as to the amount of drained blood, postoperative change in hemoglobin, postoperative complications, and knee function. Results: We found that drained blood and hemoglobin drop were significantly lower in group T compared with group C. There was no difference regarding postoperative complications and knee function. Conclusion: We conclude that tourniquet release after skin closure and compressive dressing followed by 6h of drain clamping reduces postoperative blood loss in TKR surgery.